Private Donations for Public Transit: The Equity Implications of Detroit's Public–Private Streetcar. (September 2020) - Lowe, Kate; Grengs, Joe
Transportation agencies are increasingly seeking private sector funding, but resulting deals have implications beyond specific projects. We analyze the broader regional and equity impacts of private funding by examining Detroit's donation-funded streetcar. Despite potential negative consequences for transit-dependent populations, the longer-term political will forged through streetcar planning has a contingent possibility to enhance regional transit. In addition to donations, the streetcar relies on public sector funds, but we found limited public influence to ensure collective transportation benefits. A federal-level actor did mandate that a regional transit agency form, but more systematic public action is needed.